TAFSIR AL-QUR’AN DI MEDIA SOSIAL (Karakteristik Penafsiran Pada Akun Media Sosial @Quranreview) - Nurdin, Rahmat (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
@Quranreview is an account that specifically creates content and posts about verses of the Qur’an and their placement using social media as a medium to express them. In this study using qualitative methods based on literature review with reference ti the content of posts, writings and studies from the @Quranreview account. In addition, it also refers ti books, journals and theses as additional references. In this study using discourse theory. The results on this study show the relationship between interpretation and social media, the types of social media used in uncovering the verses of the Qur’an such as social networking, media sharing, blogs, and the web. Social media as a medium of discourse in assisting interpretation. The influence of social media on the interpretation of developments is that it can make it easier for people to learn and study the Qur’an because it can be accessed anywhere and anytime. The background of the rapid development of social media interpretation is the difference in how discovery works in the form of books and social media. Social media interpretation has three tendencies, namely contextual, textual and scientific interpretation which were originally carried out by the authorities of scholars, academics and intellectuals but now the general public or lay people get involved in it. The interpretation method on this account uses a thematic method which is presented in audiovisual form and visual with a linguistic pattern that is so thick in its locking, the characteristics of the interpretation of this account use the thematic method and are very thick with a linguistic approach in the discussion of its interpretation.